Perancangan Sistem Manajemen Restoran Berbasis Web Menggunakan Metode Agile (Studi Kasus : Nasi Goreng 351) - Fawaz Faruq Arrasyad, Muhamad Irza; Anwar, Chairul (PT Jurnal Cendekia Indonesia, 2026)
This research aims to design and develop a web-based restaurant management system at kedai Nasi Goreng 351 using the Agile method. The problems faced are the recording of sales transactions that are still carried out manually and the lack of integration of sales data between branches, making it difficult to monitor, report, and make decisions difficult. The Agile method is applied because it is able to support the development of the system iteratively, flexibly, and adaptively to changing user needs through a short sprint cycle. The system is designed to record sales transactions in a computerized manner and integrate data from four branches into one centralized system. The re sults of the study show that this web-based sales information system is able to improve the accuracy of transaction recording, speed up the recapitulation process, and reduce errors that often occur in manual recording. Data integration between branches allows business owners to monitor turnover and sales performance in real-time. In addition, the developed system improves transparency and control of sales, as well as provides accurate and timely information as the basis for managerial decision-making. Thus, this system is effective in supporting the management of multi-branch restaurant businesses in a more efficient and integrated manner.